2015
DOI: 10.3748/wjg.v21.i31.9273
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic full-thickness resection: Current status

Abstract: Conventional endoscopic resection techniques such as endoscopic mucosal resection or endoscopic submucosal dissection are powerful tools for treatment of gastrointestinal neoplasms. However, those techniques are restricted to superficial layers of the gastrointestinal wall. Endoscopic full-thickness resection (EFTR) is an evolving technique, which is just about to enter clinical routine. It is not only a powerful tool for diagnostic tissue acquisition but also has the potential to spare surgical therapy in sel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
59
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(61 citation statements)
references
References 78 publications
0
59
0
2
Order By: Relevance
“…Several endoscopic techniques have been reported for closure of the defect such as clips, endoloop and clips, over-the-scopeclips and endoscopic suturing devices. While most of these techniques require specialized equipment and demand a skillful handling, closure with clips is still widely accepted (6)(7)(8)(9)16,22,23). In the present study, the defects of the 28 EFTR cases were all successfully closed with clips.…”
Section: Discussionmentioning
confidence: 73%
See 2 more Smart Citations
“…Several endoscopic techniques have been reported for closure of the defect such as clips, endoloop and clips, over-the-scopeclips and endoscopic suturing devices. While most of these techniques require specialized equipment and demand a skillful handling, closure with clips is still widely accepted (6)(7)(8)(9)16,22,23). In the present study, the defects of the 28 EFTR cases were all successfully closed with clips.…”
Section: Discussionmentioning
confidence: 73%
“…ESD was used to treat gastric SMTs originating from the superficial MP layer. However, when the tumor originates from the deep MP layer or has a tight connection with the underlying MP layer or serosal layer, the complete resection rate decreases and the complication rate increases (4,16,17). Although ESE could improve the complete resection rate for gastric SMTs from the deep MP layer, it has some limitations for lesions with a tight connection with the serosal layer or with an extraluminal growth (4,18).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the OTSC (Ovesco Endoscopy GmbH, Tüebingen, Germany), a clip-shaped full-thickness suturing device, is also commercially available. A number of reports have mentioned about fistulas or closure of iatrogenic perforations and closure of anastomotic leakage after surgery [44,45,46]. This information suggested that there is no available ideal suturing device.…”
Section: Development Of Suturing Systems For Flexible Endoscopementioning
confidence: 99%
“…[3][4][5] The main limiting factor of this minimally invasive approach is subsequent secure defect closure after EFTR, which may be technically difficult for complex resections with the currently available endoluminal devices. 6 Laparoscopic endoscopic cooperative surgery (LECS) is a hybrid approach initially introduced by Hiki et al 7 as a minimally invasive technique for the resection of SETs. With LECS, the location of the lesion is first confirmed endoscopically followed by endoscopic submucosal dissection (ESD).…”
mentioning
confidence: 99%